2017
DOI: 10.1111/ajo.12757
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone concentrations and dosage with frozen embryo transfers – What's best?

Abstract: Improved pregnancy outcomes are seen with day 16 serum progesterone concentrations >50 nmol/L. There is a statistically significant correlation between live births, number of progesterone doses per day and day 16 serum progesterone concentrations in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
2
27
2
Order By: Relevance
“…Thus clinicians could optimize intramuscular progesterone supplementation according to the P monitoring. Our findings confirmed previous data that luteal progesterone level outside the range limits reduced clinical pregnancy rate (40)(41)(42). But we further explored newborn birthweight and gestational age in this intramuscular progesterone cohort and revealed that systemic P level higher than 41.82 pmol/L did not increase birthweight or prolong gestational weeks, but it increased the live birth rate.…”
Section: Interpretation Of Datasupporting
confidence: 91%
“…Thus clinicians could optimize intramuscular progesterone supplementation according to the P monitoring. Our findings confirmed previous data that luteal progesterone level outside the range limits reduced clinical pregnancy rate (40)(41)(42). But we further explored newborn birthweight and gestational age in this intramuscular progesterone cohort and revealed that systemic P level higher than 41.82 pmol/L did not increase birthweight or prolong gestational weeks, but it increased the live birth rate.…”
Section: Interpretation Of Datasupporting
confidence: 91%
“…However, which is the best scheme sitll unclear. In fact, the supraphysiological dose of hormones utilised in assisted reproductive technology (ART) procedures especially steroid hormone concentrations in the first trimester (oestradiol (E2), prolactin, progesterone (P)), and patient fertility-related problems may influence pregnancy, obstetric and neonatal outcomes [25][26][27][28]. Therefore, we aimed to determine whether AC-FET increases the risk of adverse pregnancy, obstetric and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings confirmed previous data that serum higher progesterone level during mid-luteal phase got higher successful rate than the lower P level counterparts in HRT-FET cycles. Luteal progesterone level outside the range limits reduced clinical pregnancy rate [24][25][26]. We further explored newborn birthweight and gestational age in intramuscular progesterone cohort.…”
Section: Discussionmentioning
confidence: 99%